2018
DOI: 10.3389/fphys.2018.01169
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From Human Cardiac Progenitor Cells for Therapeutic Applications: Development of a GMP-Grade Manufacturing Method

Abstract: Exosomes, nanosized membrane vesicles secreted by cardiac progenitor cells (Exo-CPC), inhibit cardiomyocyte apoptosis under stress conditions, promote angiogenesis in vitro, and prevent the early decline in cardiac function after myocardial infarction in vivo in preclinical rat models. The recognition of exosome-mediated effects has moved attempts at developing cell-free approaches for cardiac repair. Such approaches offer major advantages including the fact that exosomes can be stored as ready-to-use agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(120 citation statements)
references
References 31 publications
2
118
0
Order By: Relevance
“…The first evidence of this has been recently performed for CPC-EVs. Indeed, human CPCs cultured in xeno-free conditions showed production of EVs with similar features as in research-grade conditions [228]. The GMP method guaranteed high exosome yield (>1013 particles) by isolating through a closed system of ultrafiltration, and consistent removal (≥97%) of contaminating proteins.…”
Section: Conclusion: Challenges To Be Overcomementioning
confidence: 82%
See 2 more Smart Citations
“…The first evidence of this has been recently performed for CPC-EVs. Indeed, human CPCs cultured in xeno-free conditions showed production of EVs with similar features as in research-grade conditions [228]. The GMP method guaranteed high exosome yield (>1013 particles) by isolating through a closed system of ultrafiltration, and consistent removal (≥97%) of contaminating proteins.…”
Section: Conclusion: Challenges To Be Overcomementioning
confidence: 82%
“…Moreover, one of the most relevant therapeutic advantage of EVs, compared to the parental cells, is their potential to "escape" to the immune system. The absence of costimulatory molecule MHC-II gives EVs the potential to escape recognition by CD4 lymphocytes [90,216,228], although this aspect needs more detailed investigation.…”
Section: Conclusion: Challenges To Be Overcomementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Pachler et al (2017) developed a GMP standard protocol for human MEVs. More recently, a GMP-grade method for the large-scale preparation of EVs from human cardiac progenitor cells was described (Andriolo et al, 2018). Additionally, Mendt et al (2018) reported a bioreactor-based, large-scale production protocol of clinical-grade exosomes employing GMP standards.…”
Section: Insufficient Clinical Grade Productionmentioning
confidence: 99%
“…Following isolation, current assessments of exosome identity involve an extensive profiling of characteristic surface proteins on both the exosomes and parental cells. Western blotting or flow cytometry can be used to assess the presence of exosome surface proteins (e.g., CD9, CD63, CD81) on the isolated particles, while parental cells are characterized for viability and cell surface marker profiles [33]. Microscopy techniques, such as electron microscopy (EM) and atomic force microscopy (AFM), may be useful for additional morphology and size distribution characterization [32].…”
Section: Exosome Isolation and Characterizationmentioning
confidence: 99%